Sistem Penataan Arsip Dinamis pada Subbagian Penentuan Bidang Pidana Umum Pengadilan Negeri Payakumbuh - Anzhori, Giant; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
Structuring Systems Archive Dynamic Field In Sub-Section Determination General Crime In Court Payakumbuh. Program of Library and Information Science Studies Archives, Department of Language and Literature Indonesia and the Region, the Faculty of Languages ​​and Arts, State University of Padang. The problem of this paper is how to setup the system records and constraints faced in the structuring and implementation of archival records at the District Court Payakumbuh. The purpose of writing this paper aims to describe the arrangement of the system records the Subdivision Determination District Court Foreign Affairs Criminal Payakumbuh. The method used for writing this paper uses descriptive method is to describe on an object as it is at any given time. The data obtained through the survey directly to the arrangement of records at the District Court Payakumbuh. For that obtain accurate data conducted interviews directly. Keywords: archive ; system records